Improvement of the gait pattern after selective dorsal rhizotomy derives from changes of kinematic parameters in the sagittal plane - Jiang, Wenbin; Jiang, Shuyun; Yu, Yan; Zhan, Qijia; Wei, Min; Mei, Rong; Chen, Fang; Guo, Yao; Xiao, Bo (Frontiers in Pediatrics, 2022)
Objective: Selective dorsal rhizotomy (SDR) can decrease spasticity in children suffering from spastic cerebral palsy (SCP) and thus improve their moving ability when supplemented with the post-operational rehabilitation program. In this case, the study aims to investigate the gait changes in children with mild SCP after SDR in short-term follow-up. Methods: The information of ambulatory SCP cases who underwent SDR in our center was retrospectively reviewed, and comparisons of changes in spasticity, motor function and data of gait analysis before and after SDR were analyzed. Results: In total, 32 cases were included in this study, with a mean age of 5.9 ± 2.1 years old. Noticeable decrease was found in the median value of the pre-operational MAS score after SDR at last follow-up in both sides of adductors, gastrocnemius, soleus, and left hamstrings. The Gross Motor Function Measure-66 score increased from 70.6 ± 9.2 to 73.4 ± 8.2, and the gait deviation index increased after SDR compared with the pre-operational data (right side: 65.8 ± 8.8 vs. 60.1 ± 10.7; left side: 63.5 ± 10.1 vs. 57.0 ± 9.9). Noticeable changes were found that the maximum angle of affected ankles in the sagittal plane (the dorsal-flexion angle) increased from 2.5° to 8.2°, the angles at initial contact (1% gait cycle) of affected knees in the sagittal plane decreased from 34.0° to 27.8°, and the angles at the end of swing phase (100% gait cycle) of affected knees in the sagittal plane decreased from 35.8° to 28.3°. Conclusions: In short-term follow-up, SDR can lower spasticity in children with SCP. Post-operational gait analysis showed improvements in gross motor function and gait, which derived from the changes in the sagittal plane (ankle and knee). A longer follow-up duration is thus needed to clarify the long-term outcome.